Discovery of pyrazolopyrimidine phosphodiesterase 10A inhibitors for the treatment of schizophrenia. Issue 1 (1st January 2016) - Raheem, Izzat T.; Schreier, John D.; Fuerst, Joy; Gantert, Liza; Hostetler, Eric D.; Huszar, Sarah; Joshi, Aniket; Kandebo, Monika; Kim, Somang H.; Li, Jing; Ma, Bennett; McGaughey, Georgia; et al.
Graphical abstract: Abstract: Herein, we present the identification of a novel class of pyrazolopyrimidine phosphodiesterase 10A (PDE10A) inhibitors. Beginning with a lead molecule (1 ) identified through a fragment-based drug discovery (FBDD) effort, lead optimization was enabled by rational design, X-ray crystallography, metabolic and off-target profiling, and fragment scaffold-hopping. We highlight the discovery ofPyP-1, a potent, highly selective, and orally bioavailable pyrazolopyrimidine inhibitor of PDE10A.PyP-1 exhibits sub-nanomolar potency (PDE10A K i  = 0.23 nM), excellent pharmacokinetic (PK) and physicochemical properties, and a clean off-target profile. It displays dose-dependent efficacy in numerous pharmacodynamic (PD) assays that measure potential for anti-psychotic activity and cognitive improvement.PyP-1 also has a clean preclinical profile with respect to cataleptic potential in rats, prolactin secretion, and weight gain, common adverse events associated with currently marketed therapeutics. Further, PyP-1 displays in vivo preclinical target engagement as measured by PET enzyme occupancy in concert with[ 11 C]MK-8193, a novel PDE10A PET tracer.